FORMULASI DAN EVALUASI FISIK TABLET EKSTRAK ETANOL DAUN SALAM (EUGENIA POLYANTHA W.) DENGAN METODE GRANULASI BASAH - Nor Latifah; Hayatus Sa’adah; Sri Rahayu (Sekolah Tinggi Pariwisata Mataram, 2022)
Eugenia polyantha W or often known as salam leaf, contains flavonoid compounds, tannins and eugenol which are used to lower blood glucose levels. Natural ingredients are less practical in their use, therefore it is necessary to make preparations such as tablets. The purpose of this study was to determine the formulation of salam leaf extract tablets using the wet granulation method. The independent variables of this study were using dry extract of salam leaf as the active substance and gelatin as a binder in tablets with a concentration of 5% and 10%. The dependent variable is the physical evaluation of tablets including weight uniformity, hardness and friability. The results of the research on formula 1 that met the requirements were only on evaluation of weight uniformity, and on formula 2 which met the requirements only evaluation of weight uniformity and evaluation of hardness. So that the resulting tablet can be stated that formula 2 produces better evaluation results than formula 1.